AKTIVITAS ANTIBAKTERI EKSTRAK KELOPAK BUAH DENGEN (Dillenia serrata Thunb.) TERHADAP Escherichia coli DAN Staphylococcus aureus - Boy Rahardjo Sidharta (Scripta Biologica, 2019)
AbstRactDillenia serrata (Dengen) is an endemic plant from Sulawesi and it has never been known for its benefit, especially as antibacterial herbs. Unripe Dengen’s fruit is enveloped by sepals, thus it is indicated to have antibacterial activity as a protection of fruit from destructive bacteria. This research aimed to determine the optimum inhibitory of Dengen fruit sepals extracts to Escherichia coli and Staphylococcus aureus. Fruit sepals were extracted with two solvents, which are polar and non-polar, namely methanol and n-hexane. The extraction was done by maceration. Compounds from methanol and n-hexane extracts were qualitatively measured using phytochemical test, such as alkaloid, flavonoid, tannin, triterpenoid/steroid, and saponin. Methanol and n-hexane extracts were divided into three concentrations as treatments for antibacterial test namely 30, 60, and 90 % using disk diffusion method with five replications. The result of phytochemical test showed Dengen fruit sepals contained alkaloids, flavonoids, tannins, triterpenoids/steroids and saponins. The extracts showed optimum inhibitory effect to E. coli which was obtained at 90 % of methanol extract with 0.495 cm inhibitory zone diameter. While, the optimum inhibitory effect to S. aureus was obtained at 90 % of n-hexane extract with 0.54 cm of inhibitory zone diameter. Key words: Dengen fruit sepals, antibacterial, maceration, phytochemical, disk diffusion method